2019
DOI: 10.1093/foresj/cpz056
|View full text |Cite
|
Sign up to set email alerts
|

A recruitment model for beech–oak pure and mixed stands in Belgium

Abstract: We present a recruitment model for pure and mixed beech and oak stands in Belgium, the first empirical model for this forest type in this geographical area. Data from the Wallonia National Forest Inventory were used to fit the model. We adopted a zero-inflated formulation where model parameters governing species’ behaviour were simultaneously fitted. Plot random effects specific to each species were included, the simultaneous fit allowing them to correlate. Model predictions proved accurate and corresponded to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
3
6
0
2
Order By: Relevance
“…In particular, the decreasing survival probabilities indicated the need for silvicultural assistance in the given stand situations (see Figure 2). Accordingly, the participation of oak in a mixture with beech was not stable throughout the regeneration period and confirmed the results of some studies [18,19,39,49], which can also be found in the early silvicultural principles for oak management [18,25,50]. Differences between experimental sites and forest stand types were clearly recognizable and should be considered in pre-commercial thinnings.…”
Section: Long-term Development and Survival Of The Regenerationsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, the decreasing survival probabilities indicated the need for silvicultural assistance in the given stand situations (see Figure 2). Accordingly, the participation of oak in a mixture with beech was not stable throughout the regeneration period and confirmed the results of some studies [18,19,39,49], which can also be found in the early silvicultural principles for oak management [18,25,50]. Differences between experimental sites and forest stand types were clearly recognizable and should be considered in pre-commercial thinnings.…”
Section: Long-term Development and Survival Of The Regenerationsupporting
confidence: 83%
“…These observations were also made for even younger oak regenerations [34,53]. Accordingly, oak requires the support of the silvicultural regulation of woody competitors for successful establishment in many sites [18,49,54].…”
Section: Influence Of Canopy Cover and Interspecific Competitionmentioning
confidence: 96%
“…Several studies have shown the impact of surrounding stand composition (Petritan et al, 2012;Annighöfer et al, 2015;Manso et al, 2020) or of distance from the gap edge on the density of oak and beech saplings in canopy gaps (Van Couwenberghe et al, 2010;Tinya et al, 2020). To date, very few studies (Tinya et al, 2020) have quantified these patterns for hornbeam.…”
Section: Introductionmentioning
confidence: 99%
“…However, a preliminary check of the data showed that there were many more zero counts than would be expected at random from a Poisson distribution. This is known as "zero inflation" and it is a common issue in regeneration data [30,31]. Ignoring this excess of zeros would lead to biased parameter estimates and standard errors.…”
Section: Discussionmentioning
confidence: 99%